Self-adhesive, stretchable waterborne polyurethane-based flexible film as wearable conformal strain sensor for motion and health monitoring - Xing, Linlong; Wang, Xin; Li, Mingzhan; Jia, Yunpeng; Yang, Guanda; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Advanced Nanocomposites, 2024)
Wearable tensile strain sensors are of great importance in both motion monitoring and next-generation, personalized health diagnostics. The accuracy, reliability and stability of the signals obtained from these sensors are significantly dependent on the conformal contact between the flexible sensor and the skin surface. In this study, we have developed a flexible double-layer film as a wearable tensile strain sensor by a simple solution-blending method and a layer-by-layer spraying method. D-sorbitol was incorporated into a waterborne polyurethane (WPU) emulsion to enhance film adhesion, achieving a strength of 7.91 N/m, and to disrupt hydrogen bonds between the WPU chains. This disruption facilitates more straightforward conformational changes of the chains under stress, thereby substantially enhancing the mechanical flexibility of the film. The sensing layer was subsequently constructed by spraying silver microparticles, exhibiting extremely high sensitivity (gauge factor = 103.01) over a 19.3% strain range. This sensor can effectively monitor joint motions and subtle muscle movements as tensile strain sensors.<br
Keywords: D-sorbitol; Waterborne polyurethane; Self-adhesive; Strain sensors; Motion and health monitoring